A self-cleaning anti-reflection coating solution and its preparation method and application

By modifying the self-cleaning and permeability-enhancing coating solution formed by composite of silica and acrylic, the problems of insufficient oleophobicity and poor weather resistance in the prior art are solved, and the coating performance of high light transmission, hydrophilic self-cleaning and high weather resistance are achieved, and the power generation efficiency and cleaning cost of photovoltaic glass are improved.

CN119144201BActive Publication Date: 2025-04-25SHANGHAI HUZHENG IND CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411629896.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-04-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing self-cleaning coatings mainly rely on hydrophobicity, resulting in insufficient oleophobicity, difficult to remove non-aqueous dust/dirt, and poor weather resistance.

Method used

A self-cleaning and permeability coating solution is developed to form monomer units by modifying silica and acrylic acid, participate in the polymerization of acrylate resin, prepare a silica composite resin emulsion, and mix it with adhesion promoter and water to form a hydrophilic self-cleaning and permeability coating.

Benefits of technology

It realizes coating performance with high light transmission, hydrophilic self-cleaning and high weather resistance, solves the problems of insufficient oleophobicity and poor weather resistance, and improves the power generation efficiency and cleaning cost of photovoltaic glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The present application discloses a self-cleaning anti-reflective coating liquid and its preparation method and application, which belong to the field of photovoltaic glass technology. The self-cleaning anti-reflective coating liquid, by weight, includes the following components: silica composite resin emulsion: 100-120 parts; adhesion promoter: 0.5-2 parts; water: 10-20 parts. The self-cleaning anti-reflective coating liquid has the effects of hydrophilic self-cleaning and improving the transmittance of incident light. The composite functional component is mainly modified silica composite amphiphilic acrylic resin, which is compounded by silica modification, acrylic monomer modification and emulsion polymerization. The prepared self-cleaning anti-reflective coating liquid is used for surface coating of plastic film, glass, etc., and can achieve the functions of hydrophilicity (contact angle ≤5°), anti-reflection rate 3%, and high weather resistance (QUV≥500h), and has broad market application prospects in the photovoltaic glass industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a self-cleaning anti-reflection coating liquid and a preparation method and application thereof, belonging to the technical field of photovoltaic glass. Background Art

[0002] Solar energy can be used as a clean energy source for photovoltaic power generation, which can reduce environmental pollution and resource waste caused by thermal power generation. When sunlight passes through photovoltaic glass, it often refracts and reflects, resulting in a reduction in transmitted light, which affects power generation efficiency. At the same time, the surface of photovoltaic glass needs to be kept clean to avoid affecting light reception and reducing power generation. Therefore, it is necessary to develop a self-cleaning anti-reflective coating. This not only improves power generation efficiency, but also reduces cleaning costs, which significantly promotes the development and application of photovoltaic power generation.

[0003] Chinese patent CN114231177B discloses a self-cleaning coating, which is formed by cross-linking and curing of silicon dioxide, titanium dioxide and a variety of silane compounds, and has the characteristics of hydrophobicity, oleophobicity and high light transmittance. Chinese patent CN110451819B discloses a self-cleaning coated glass, the surface of which is composed of a layer of anti-reflective silicon dioxide film and a layer of modified silicon dioxide gel super-hydrophobic coating, which has the functions of hydrophobicity and anti-reflection. Chinese patent CN114163907B discloses a self-cleaning coating, which is formed by carbon alcohol-terminated fluorinated polysiloxane and polyester polyol, and has the self-cleaning function of high light transmittance and low surface energy. Most of the current research uses hydrophobicity as the main functional means of self-cleaning, and the oleophobicity is relatively insufficient. Non-aqueous dust / dirt is still easy to adhere to the surface, and water droplets are difficult to contact and wash away, thereby affecting the light transmittance; at the same time, the hydrophobic layer is often easily affected by the environment, and the weather resistance is generally not strong. Therefore, it is very necessary to develop a hydrophilic self-cleaning anti-reflective coating. Water droplets can spread on the surface of the coating to form a water film, infiltrating or washing away dirt, and the coating also has the weather resistance advantage of a more stable coating. Summary of the invention

[0004] According to one aspect of the present application, a self-cleaning anti-reflection coating liquid is provided, which has good hydrophilic self-cleaning and anti-reflection effects, is used on the surface of materials such as glass, and has outstanding properties of self-cleaning, high light transmittance, and high weather resistance.

[0005] The self-cleaning anti-reflection coating solution described in this application includes the following components by weight:

[0006] Silica composite resin emulsion: 100-120 parts;

[0007] Adhesion promoter: 0.5-2 parts;

[0008] Water: 10-20 parts.

[0009] Optionally, the adhesion promoter is epoxy oligosiloxane and / or aminosiloxane.

[0010] Optionally, the silica composite resin emulsion includes a silica composite resin;

[0011] The silica composite resin contains hydroxyl groups. The structure of the silica composite resin is: in, The polymer chain structure is , R1 is an alkyl group having 1 to 4 carbon atoms, and R2 is an alkyl group having 2 to 3 carbon atoms.

[0012] Optionally, the method for preparing the silica composite resin emulsion described in the present application comprises the following steps:

[0013] (1) reacting a mixed solution 1 including tetraethyl orthosilicate, an alkaline catalyst, γ-aminotriethoxysilane and a solvent 1 to obtain modified silicon dioxide;

[0014] (2) stirring a mixture 2 including modified silica, acrylic acid, a coupling agent, and a solvent 2 to obtain an acrylic acid-silica monomer;

[0015] (3) A mixture 3 including an acrylic acid-silica monomer, a surfactant, an initiator, a pH adjuster, a solvent 3, and an acrylic acid monomer mixture I is reacted II, and then the acrylic acid monomer mixture II is added to react III, and the mixture is sieved to obtain a silica composite emulsion.

[0016] Optionally, in step (1), the alkaline catalyst is aqueous ammonia.

[0017] Optionally, the concentration of the ammonia water is 20-30wt%; preferably, the concentration of the ammonia water is 25wt%.

[0018] Optionally, solvent 1 is an alcohol solvent; preferably, the alcohol solvent is ethanol.

[0019] Optionally, in step (1), the mass ratio of tetraethyl orthosilicate, alkaline catalyst and γ-aminotriethoxysilane is (1-2): (0.3-0.6): (0.2-0.5).

[0020] Optionally, in step (1), the mass ratio of solvent 1 to tetraethyl orthosilicate is (1-2): (10-15).

[0021] Optionally, the temperature of reaction I is 40-50°C.

[0022] Optionally, the reaction time is 24-48 hours.

[0023] Optionally, the step (1) comprises: according to the mass ratio, 1-2 parts of tetraethyl orthosilicate are added dropwise to 7-10 parts of solvent 1 to form solution A, 0.3-0.6 parts of ammonia water are added dropwise to 1-3 parts of solvent 1 to form solution B, and 0.2-0.5 parts of γ-aminotriethoxysilane are added dropwise to 2-5 parts of solvent 1 to form solution C; solution A is added dropwise to solution B at room temperature, stirred for 10-30 minutes, solution C is added to the mixed solution at 40-50°C, stirred for 1-3 hours, and aged at room temperature for 24-48 hours; and modified silica is obtained after filtering, washing and drying.

[0024] Optionally, in step (2), the coupling agent includes 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide.

[0025] Optionally, the weight ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide to N-hydroxysuccinimide is (2-4):(1.5-3).

[0026] Optionally, in step (2), solvent 2 is N,N'-dimethylacetamide.

[0027] Optionally, in step (2), the weight ratio of modified silica, acrylic acid and coupling agent is (1-2): (1-3): (3.5-7).

[0028] Optionally, in step (2), the weight ratio of modified silica to solvent 2 is (1-2): (60-150).

[0029] Optionally, step (2) comprises: according to the mass ratio, 1-2 parts of modified silica are dispersed in 30-80 parts of solvent 2 to form dispersion D, 1-3 parts of acrylic acid are dissolved in 20-50 parts of solvent 2 to form solution E; 2-4 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide are dissolved in 10-20 parts of solvent 2 to form solution F; 1.5-3 parts of N-hydroxysuccinimide are added to solution E and stirred for 1-2 hours; dispersion D and solution F are simultaneously added dropwise to solution E and stirred at room temperature for 24-48 hours. After centrifugation, washing and drying, acrylic acid-silica monomer is obtained.

[0030] Optionally, in step (3), the surfactant is selected from any one or more of polyethylene glycol, sodium lauryl sulfate, and nonylphenol polyoxyethylene ether.

[0031] Optionally, in step (3), the surfactant includes polyethylene glycol, sodium lauryl sulfate, and nonylphenol polyoxyethylene ether.

[0032] Optionally, the weight ratio of polyethylene glycol, sodium lauryl sulfate and nonylphenol polyoxyethylene ether is (0.1-0.3):(0.1-0.3):(0.2-0.4).

[0033] Optionally, the number average molecular weight of the polyethylene glycol is 500-1000.

[0034] Optionally, in step (3), the initiator is ammonium persulfate.

[0035] Optionally, in step (3), the pH adjuster is sodium bicarbonate.

[0036] Optionally, in step (3), solvent 3 is water.

[0037] Optionally, in step (3), the acrylic monomer mixture I comprises alkyl acrylate and hydroxyalkyl acrylate in a weight ratio of (2-4):1.

[0038] Optionally, in step (3), the acrylic monomer mixture II comprises alkyl acrylate and hydroxyalkyl acrylate in a mass ratio of 1:(3-4).

[0039] Optionally, the alkyl acrylate is selected from any one or more of methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, and isobutyl acrylate.

[0040] Optionally, the hydroxyalkyl acrylate is hydroxyethyl acrylate and / or hydroxypropyl acrylate.

[0041] Optionally, in step (3), the weight ratio of acrylic acid-silica monomer, surfactant, initiator, pH adjuster, acrylic acid monomer mixture I, and acrylic acid monomer mixture II is (1-2): (0.4-1): (0.05-0.1): (0.05-0.1): (1-3): (2-5).

[0042] Optionally, in step (3), the weight ratio of acrylic acid-silicon dioxide monomer to solvent 3 is (1-2): (60-110).

[0043] Optionally, the temperature of reaction II is 50-60°C.

[0044] Optionally, the reaction time of II is 0.5-1h.

[0045] Optionally, the temperature of reaction III is 50-60°C.

[0046] Optionally, the reaction time of III is 2-3h.

[0047] Optionally, step (3) comprises: according to the mass ratio, 1-2 parts of acrylic acid-silica monomer and 0.1-0.3 parts of polyethylene glycol with a molecular weight of 500-1000 are ultrasonically dispersed in 50-90 parts of water to form a dispersion G. 0.05-0.1 parts of ammonium persulfate, 0.1-0.3 parts of sodium dodecyl sulfate, 0.2-0.4 parts of nonylphenol polyoxyethylene ether, and 0.05-0.1 parts of sodium bicarbonate are dissolved in 10-20 parts of water to form a solution H; under a nitrogen atmosphere, the dispersion G and the solution H are uniformly mixed. The temperature is raised to 50-60°C, and 1-3 parts of acrylic acid monomer mixture I are added under high-speed stirring. After reacting for 0.5-1h, 2-5 parts of acrylic acid monomer mixture II are added; the reaction is stopped after 2-3h, and the silica composite resin emulsion is obtained by passing through a 200-mesh sieve.

[0048] In another aspect, the present application provides a method for preparing the self-cleaning anti-reflection coating liquid, comprising: mixing a silicon dioxide composite resin emulsion, an adhesion promoter and water to obtain the self-cleaning anti-reflection coating liquid.

[0049] In another aspect, the present application provides a self-cleaning anti-reflective coating, which is prepared from the self-cleaning anti-reflective coating liquid.

[0050] In another aspect, the present application provides a self-cleaning coated photovoltaic glass, which comprises glass and the self-cleaning anti-reflection coating;

[0051] The self-cleaning coating is coated on the glass surface.

[0052] The beneficial effects of this application include:

[0053] (1) The self-cleaning anti-reflection coating liquid prepared by the present application utilizes modified silica and acrylic acid to form monomer units, participates in the polymerization of acrylic resin, thereby preparing a silica composite resin emulsion, and uniformly mixes with adhesion promoters and water and other components to form a stable self-cleaning anti-reflection coating on the glass surface. Through the regulation of hydroxyl groups, the coating not only has an anti-reflection effect, but also has a hydrophilic self-cleaning function, which solves the problem that the prior art uses hydrophobicity as the main functional means of self-cleaning, resulting in relatively insufficient oleophobicity, non-aqueous dust / dirt still easily adheres to the surface, and water droplets are difficult to contact and wash away, thereby affecting light transmission. In addition, the composite resin of the present application and the addition of adhesion promoters, while ensuring the hydrophilic self-cleaning functionality, greatly improve the adhesion and stability of the coating on the glass surface, and its weather resistance is further improved compared to general self-cleaning coatings. Compared with the prior art, the self-cleaning anti-reflection coating liquid prepared by the present application has the following four characteristics: high light transmittance, strong hydrophilicity, good adhesion, and excellent weather resistance.

[0054] (2) The self-cleaning anti-reflection coating liquid of this application does not contain fluorine and is used for coating on surfaces such as plastic films and glass. It can achieve the functions of hydrophilicity (contact angle ≤ 5°), anti-reflection rate of 3%, and high weather resistance (QUV ≥ 500h), and has broad market application prospects in the photovoltaic glass industry.

[0055] (3) In the process of preparing the silica composite resin emulsion, the acrylic monomer mixture I is controlled to be alkyl acrylate and hydroxyalkyl acrylate, and the ratio between them is controlled to be (2-4):1. After the reaction, it is reacted with alkyl acrylate and hydroxyalkyl acrylate in a mass ratio of 1:(3-4). By regulating the reaction process, the obtained coating has good hydrophilicity, adhesion and light transmittance.

[0056] (4) The inventors discovered during the experimental study that the choice of surfactant unexpectedly has a certain degree of influence on the adhesion and hydrophilicity of the coating. When the surfactants include polyethylene glycol, sodium dodecyl sulfate, and nonylphenol polyoxyethylene ether, the resulting coating has excellent adhesion and hydrophilicity. This may be because the addition of polyethylene glycol, sodium dodecyl sulfate, and nonylphenol polyoxyethylene ether affects the polymerization reaction between molecules. DETAILED DESCRIPTION

[0057] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0058] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0059] Example 1

[0060] The preparation process of silica composite resin emulsion is as follows:

[0061] (1) 12g of ethyl orthosilicate was added dropwise to 90ml of ethanol to form solution A, 5ml of 25wt% ammonia water was added dropwise to 30ml of ethanol to form solution B, and 3g of γ-aminotriethoxysilane was added dropwise to 30ml of ethanol to form solution C. Solution A was added dropwise to solution B at room temperature and stirred for 30min. Solution C was added to the mixed solution at 45°C and stirred for 2h. The solution was aged at room temperature for 24h. The modified silica was obtained after filtration, washing and drying.

[0062] (2) 10 g of modified silica was dispersed in 400 ml of N,N´-dimethylacetamide to form dispersion D, and 21.6 g of acrylic acid was dissolved in 400 ml of N,N´-dimethylacetamide to form solution E. 27.9 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide was dissolved in 200 ml of N,N´-dimethylacetamide to form solution F. 20.7 g of N-hydroxysuccinimide was added to solution E and stirred for 2 h. Dispersion D and solution F were added dropwise to solution E at the same time and stirred at room temperature for 36 h. After centrifugal washing and drying, acrylic acid-silica monomer was obtained.

[0063] (3) 10g of acrylic acid-silica monomer and 1.5g of polyethylene glycol with a molecular weight of 750 were ultrasonically dispersed in 800ml of water to form dispersion G. 0.9g of ammonium persulfate, 2.4g of sodium dodecyl sulfate, 2g of nonylphenol polyoxyethylene ether, and 0.8g of sodium bicarbonate were dissolved in 200ml of water to form solution H. Dispersion G and solution H were uniformly mixed under nitrogen atmosphere. The temperature was raised to 60°C, and 9g of isobutyl acrylate, 5.6g of ethyl acrylate, 3.4g of methyl acrylate, and 6g of hydroxyethyl acrylate were added under high-speed stirring. After reacting for 1h, 16g of hydroxyethyl acrylate, 9.5g of hydroxypropyl acrylate, 3.2g of methyl acrylate, and 4.5g of isobutyl acrylate were added. The reaction was stopped after 3h, and the silica composite resin emulsion was obtained by passing through a 200-mesh sieve.

[0064] 1000 ml of silicon dioxide composite resin emulsion, 15 ml of aminosilicone KH-450 and 150 ml of water were mixed uniformly by high-speed stirring to prepare a self-cleaning anti-reflection coating solution. Example 2

[0065] The preparation process of silica composite resin emulsion is as follows:

[0066] (1) 15g of ethyl orthosilicate was added dropwise to 100ml of ethanol to form solution A, 6ml of 25% ammonia water was added dropwise to 27ml of ethanol to form solution B, and 3.6g of γ-aminotriethoxysilane was added dropwise to 27ml of ethanol to form solution C. Solution A was added dropwise to solution B at room temperature and stirred for 30min. Solution C was added to the mixed solution at 50°C and stirred for 3h. The solution was aged at room temperature for 24h. The modified silica was obtained after filtration, washing and drying.

[0067] (2) 10 g of modified silica was dispersed in 400 ml of N,N´-dimethylacetamide to form dispersion D, and 20.1 g of acrylic acid was dissolved in 400 ml of N,N´-dimethylacetamide to form solution E. 21.6 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide was dissolved in 200 ml of N,N´-dimethylacetamide to form solution F. 15.5 g of N-hydroxysuccinimide was added to solution E and stirred for 2 h. Dispersion D and solution F were added dropwise to solution E at the same time and stirred at room temperature for 48 h. After centrifugal washing and drying, acrylic acid-silica monomer was obtained.

[0068] (3) 10g of acrylic acid-silica monomer and 2g of polyethylene glycol with a molecular weight of 750 were ultrasonically dispersed in 850ml of water to form dispersion G. 0.9g of ammonium persulfate, 2.4g of sodium dodecyl sulfate, 2g of nonylphenol polyoxyethylene ether, and 0.8g of sodium bicarbonate were dissolved in 200ml of water to form solution H. Dispersion G and solution H were uniformly mixed under nitrogen atmosphere. The temperature was raised to 60°C, and 9g of isobutyl acrylate, 6.4g of propyl acrylate, 2.4g of methyl acrylate, and 5.6g of hydroxyethyl acrylate were added under high-speed stirring. After reacting for 1h, 18g of hydroxyethyl acrylate, 10g of hydroxypropyl acrylate, 2.8g of methyl acrylate, and 4.2g of isobutyl acrylate were added. The reaction was stopped after 3h, and the silica composite resin emulsion was obtained by passing through a 200-mesh sieve.

[0069] 1000 ml of silicon dioxide composite resin emulsion, 13 ml of aminosilicone KH-450 and 160 ml of water were mixed uniformly by high-speed stirring to prepare a self-cleaning anti-reflection coating solution. Example 3

[0070] The preparation process of silica composite resin emulsion is as follows:

[0071] (1) 10g of ethyl orthosilicate was added dropwise to 90ml of ethanol to form solution A, 5ml of 25% ammonia water was added dropwise to 30ml of ethanol to form solution B, and 2.7g of γ-aminotriethoxysilane was added dropwise to 30ml of ethanol to form solution C. Solution A was added dropwise to solution B at room temperature and stirred for 30min. Solution C was added to the mixed solution at 45°C and stirred for 3h. The solution was aged at room temperature for 24h. The modified silica was obtained after filtration, washing and drying.

[0072] (2) 10 g of modified silica was dispersed in 400 ml of N,N´-dimethylacetamide to form dispersion D, and 23.7 g of acrylic acid was dissolved in 400 ml of N,N´-dimethylacetamide to form solution E. 25.5 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide was dissolved in 200 ml of N,N´-dimethylacetamide to form solution F. 19 g of N-hydroxysuccinimide was added to solution E and stirred for 2 h. Dispersion D and solution F were added dropwise to solution E at the same time and stirred at room temperature for 48 h. After centrifugation, washing and drying, acrylic acid-silica monomer was obtained.

[0073] (3) 10g of acrylic acid-silica monomer and 2g of polyethylene glycol with a molecular weight of 750 were ultrasonically dispersed in 800ml of water to form dispersion G. 0.9g of ammonium persulfate, 2.4g of sodium dodecyl sulfate, 2g of nonylphenol polyoxyethylene ether, and 0.8g of sodium bicarbonate were dissolved in 200ml of water to form solution H. Dispersion G and solution H were uniformly mixed under nitrogen atmosphere. The temperature was raised to 60°C, and 6.5g of isobutyl acrylate, 2.5g of n-butyl acrylate, 5g of methyl acrylate, and 6g of hydroxyethyl acrylate were added under high-speed stirring. After reacting for 1h, 18g of hydroxyethyl acrylate, 10g of hydroxypropyl acrylate, 2.8g of propyl acrylate, and 4.2g of isobutyl acrylate were added. The reaction was stopped after 3h, and the silica composite resin emulsion was obtained by passing through a 200-mesh sieve.

[0074] 1000 ml of silicon dioxide composite resin emulsion, 10 ml of epoxy oligosiloxane KRN8060 and 120 ml of water were mixed uniformly by high-speed stirring to prepare a self-cleaning anti-reflection coating solution.

[0075] Test example

[0076] The self-cleaning anti-reflection coating liquid prepared in each embodiment was brush-coated on a clean and dry transparent glass surface, and after drying at 120°C for 20 minutes, the coating performance was tested. The adhesion was tested by the 100-grid method, and the weather resistance was tested by the Kejian KJ-9029 UV aging box for 500 hours. The UV wavelength was 340nm, and the sample was irradiated with 4 40W UV lamps. The sample was placed 50mm away from the lamp, and the irradiance was about 50W / m 2 , 4h UV irradiation and 4h condensation alternately, the temperature is 50℃. The contact angle of the coating to water is tested to characterize its hydrophilicity, and the visible light transmittance change of the glass before and after coating is tested by Linshang spectrum tester LS182.

[0077] Table 1 Test performance of coating samples

[0078] Example 1 Example 2 Example 3 Adhesion Level 0 Level 0 Level 0 QUV500h No significant changes No significant changes No significant changes Water contact angle 4.5° 5.0° 5.0° Visible light transmittance (uncoated) 85.2% 85.2% 85.2% Visible light transmittance (with coating) 88.3% 88.2% 88.2%

[0079] The test results are shown in Table 1. The test shows that the adhesion of the coatings of Examples 1-3 reaches level 0, and the weather resistance is outstanding. The QUV500h coating has no significant change. At the same time, the contact angles are all below 5°, which makes it have a hydrophilic self-cleaning effect. A water film can be formed on the surface of the coating to effectively clean dirt and dust. Through the test of visible light transmittance, it can be seen that the coating has a significant gain in transmittance, and the average transmittance enhancement rate exceeds 3%. It has a good application prospect in related industries such as photovoltaic glass.

[0080] Example 4

[0081] The preparation process of the silica composite resin emulsion is the same as that of Example 1, except that, in step (3), 10 g of acrylic acid-silica monomer and 1.5 g of polyethylene glycol with a molecular weight of 750 are ultrasonically dispersed in 800 ml of water to form a dispersion G. 0.9 g of ammonium persulfate, 2.4 g of sodium dodecyl sulfate, 2 g of nonylphenol polyoxyethylene ether, and 0.8 g of sodium bicarbonate are dissolved in 200 ml of water to form a solution H. Under a nitrogen atmosphere, the dispersion G and the solution H are uniformly mixed. The temperature is raised to 60° C., and 13.5 g of isobutyl acrylate, 5.6 g of ethyl acrylate, 6.6 g of methyl acrylate, 22 g of hydroxyethyl acrylate, and 9.5 g of hydroxypropyl acrylate are added under high-speed stirring. After reacting for 4 hours, the mixture is sieved through a 200-mesh sieve to obtain a silica composite resin emulsion.

[0082] 1000 ml of silicon dioxide composite resin emulsion, 15 ml of aminosilicone KH-450 and 150 ml of water were mixed uniformly by high-speed stirring to prepare a self-cleaning anti-reflection coating solution.

[0083] Example 5

[0084] The preparation process of the silica composite resin emulsion is the same as that of Example 1, except that, in step (3): 10 g of acrylic acid-silica monomer and 1.5 g of polypropylene glycol PPG-600 are ultrasonically dispersed in 800 ml of water to form a dispersion G. 0.9 g of ammonium persulfate, 4.4 g of nonylphenol polyoxyethylene ether, and 0.8 g of sodium bicarbonate are dissolved in 200 ml of water to form a solution H. Under a nitrogen atmosphere, the dispersion G and the solution H are uniformly mixed. The temperature is raised to 60°C, and 9 g of isobutyl acrylate, 5.6 g of ethyl acrylate, 3.4 g of methyl acrylate, and 6 g of hydroxyethyl acrylate are added under high-speed stirring. After reacting for 1 hour, 16 g of hydroxyethyl acrylate, 9.5 g of hydroxypropyl acrylate, 3.2 g of methyl acrylate, and 4.5 g of isobutyl acrylate are added. The reaction is stopped after 3 hours, and the silica composite resin emulsion is obtained by passing through a 200-mesh sieve.

[0085] 1000 ml of silicon dioxide composite resin emulsion, 15 ml of aminosilicone KH-450 and 150 ml of water were mixed uniformly by high-speed stirring to prepare a self-cleaning anti-reflection coating solution.

[0086] Example 6

[0087] The preparation process of the silica composite resin emulsion is the same as that of Example 1, except that 10 g of modified silica is dispersed in 400 ml of N,N'-dimethylacetamide to form a dispersion D, and 21.6 g of acrylic acid is dissolved in 400 ml of N,N'-dimethylacetamide to form a solution E. The dispersion D and the solution E are mixed and stirred at room temperature for 36 hours. After centrifugal washing and drying, an acrylic acid-silica monomer is obtained.

[0088] The test results of Examples 4-6 are shown in Table 2.

[0089] Table 2 Test performance of coating samples

[0090] Example 4 Example 5 Example 6 Adhesion Level 1 Level 1 Level 2 Water contact angle 12.5° 8° 21.5° Visible light transmittance (uncoated) 85.20% 85.20% 85.20% Visible light transmittance (with coating) 85.70% 87.90% 85.30%

[0091] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A self-cleaning anti-reflection coating solution, characterized in that: By weight, it includes the following ingredients: Silica composite resin emulsion: 100-120 parts; Adhesion promoter: 0.5-2 parts; Water: 10-20 parts; The silica composite resin emulsion includes a silica composite resin; The structure of the silica composite resin is: in, The polymer chain structure is , R1 is an alkyl group having 1 to 4 carbon atoms, and R2 is an alkyl group having 2 to 3 carbon atoms; The preparation method of the silicon dioxide composite resin emulsion comprises the following steps: (1) reacting a mixed solution 1 including tetraethyl orthosilicate, an alkaline catalyst, γ-aminotriethoxysilane and a solvent 1 to obtain modified silicon dioxide; (2) stirring a mixture 2 including modified silica, acrylic acid, a coupling agent, and a solvent 2 to obtain an acrylic acid-silica monomer; (3) reacting a mixture 3 including an acrylic acid-silica monomer, a surfactant, an initiator, a pH adjuster, a solvent 3, and an acrylic acid monomer mixture I, adding the acrylic acid monomer mixture II, reacting III, and sieving to obtain a silica composite emulsion; In the step (2), the coupling agent includes 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide; The weight ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide is (2-4): (1.5-3); In the step (3), the acrylic monomer mixture I comprises alkyl acrylate and hydroxyalkyl acrylate in a weight ratio of (2-4):1; In the step (3), the acrylic monomer mixture II comprises alkyl acrylate and hydroxyalkyl acrylate in a mass ratio of 1:(3-4).

2. The self-cleaning anti-reflection coating solution according to claim 1, characterized in that: The temperature of the reaction I is 40-50°C; The temperature of the reaction II is 50-60°C; The temperature of the reaction III is 50-60°C.

3. The self-cleaning anti-reflection coating solution according to any one of claims 1 to 2, characterized in that: The adhesion promoter is epoxy oligosiloxane and / or aminosiloxane.

4. A method for preparing the self-cleaning anti-reflection coating solution according to any one of claims 1 to 3, characterized in that: include: The self-cleaning anti-reflection coating liquid is obtained by mixing the silicon dioxide composite resin emulsion, the adhesion promoter and water.

5. A self-cleaning antireflective coating, characterized in that: The self-cleaning anti-reflection coating liquid is prepared from the self-cleaning anti-reflection coating liquid according to any one of claims 1 to 3.

6. A self-cleaning coated photovoltaic glass, characterized in that: Comprising photovoltaic glass and the self-cleaning antireflective coating according to claim 5; The self-cleaning anti-reflection coating is coated on the surface of photovoltaic glass.

Citation Information

Patent Citations

  • A self-cleaning coated glass and its preparation method

    CN110451819B

  • A self-cleaning coating, its preparation method and application

    CN114163907B

  • A self-cleaning coating for solar photovoltaic panels and its preparation method

    CN114231177B

  • Quantum dot-organic silicon composite modified water-based self-cleaning coating and preparation method thereof

    CN118421155A